Needs and Purposes of library automation: A Review - Mathur, Dr Anamika (Innovative Research Thoughts, 2017)
Library is considered as heart of institution and soul of any learning institution, which is pivot of teaching-learning process. A well-equipped and well maintained library is the foundation of modern education structure. College library plays an important role in providing overall library and information services to the patrons. College libraries are the hub of the teaching and learning activities where students and teacher scan explore the vast resources of information. In the traditional libraries users have to send more time for searching a small piece of information and for that have to depend mainly on the library professional or library staff. But in the age of information communication technology, computers are being used for day-to-day housekeeping activity of the library which saves the time avoid duplication of work and make the library service smooth and effective.